Philomena [videorecording (DVD)] - Frears, Stephen; Coogan, Steve; Coogan, Steve; Coogan, Steve; Dench, Judi, 1934-; Winningham, Mare; Fairley, Michelle; Kennedy Clark, Sophie, 1989-; Lahbib, Simone, 1965-; Sixsmith, Martin
Judi Dench stars in the story of Philomena Lee, mother to a boy conceived out of wedlock and given up for adoption. Nearly 50 years later, Philomena meets Martin Sixsmith, a former BBC reporter looking for his next big story. Together, they embark on a journey to locate her long lost son. As the pieces of the puzzle come together, the unlikely travel companions form a comic and heartwarming friendship. Based on the 2009 investigative book by Martin Sixsmith.